License to Cheat: Voluntary Regulation and Ethical Behavior - Gino, Francesca; Krupka, Erin L.; Weber, Roberto A. (Management Science, 2013)
Although monitoring and regulation can be used to combat socially costly unethical conduct, their intended targets can often avoid regulation or hide their behavior. This surrenders at least part of the effectiveness of regulatory policies to firms' and individuals' decisions to voluntarily submit to regulation. We study individuals' decisions to avoid monitoring or regulation and thus enhance their ability to engage in unethical conduct. We conduct a laboratory experiment in which participants engage in a competitive task and can decide between having the opportunity to misreport their performance or having their performance verified by an external monitor. To study the effect of social factors on the willingness to be subject to monitoring, we vary whether participants make this decision simultaneously with others or sequentially, as well as whether the decision is private or public. Our results show that the opportunity to avoid being submitted to regulation produces more unethical conduct than situations in which regulation is either exogenously imposed or entirely absent. This paper was accepted by Uri Gneezy, behavioral economics.